PENGARUH PEER EDUCATOR DENGAN TENAGA KESEHATAN TERHADAP TINGKAT PENGETAHUAN DAN SIKAP REMAJA TENTANG HIV/AIDS DI SMAN 2 KECAMATAN TBT - Rini Budiarti; Christin Angelina Febiani; Wayan Aryawati (Jurnal Keperawatan dan Kesehatan, 2022)
ABSTRACT One of the deadliest pandemics is HIV/AIDS. In 2020, as many as 680,000 people died of AIDS-related diseases and 1.5 million people were newly infected with HIV.(UNAIDS, 2021). The percentage of HIV/AIDS cases according to the productive age group (15-49 years) was 2.9%, dominating the distribution of both HIV and AIDS cases.(MOH RI, 2021). Cases of HIV/AIDS continue to increase in adolescents so that the importance of adolescent knowledge in preventing HIV/AIDS. One of the methods used is the role of peer educator, health workers have the main task of providing education to schools. Starting from this, the counseling approach can change the process of thinking, feeling and healthy behavior. The purpose of the study was to determine the differences in the level of knowledge and attitudes of adolescents about HIV/AIDS before and after peer educator, health worker and control education were conducted at SMAN2 TBT District. This type of quantitative research with a “quasi-experimental” approach takes measurements before and after the education of peer educators, health workers, controls. The population is 314 students. The sampling technique used was simple random sampling. 90 students were divided into 3 groups, namely peer educator, health worker, and control groups. The research instrument was a questionnaire from the 2017 IDHS. The analysis was carried out using univariate, bivariate and multivariate methods. The results showed that there was an effect of increasing adolescent knowledge and attitudes about HIV/AIDS with p-value = 0.001 (<0.05). There are differences in the level of knowledge and attitudes of adolescents with p-value = 0.001 (<0.05). The group that has the most influence on adolescent knowledge is the control group, p-value 0.014 (<0.05). Meanwhile, the attitude of adolescents does not exist because the p-value is 0.502 (> 0.05). Suggestion: regular training, monitoring and evaluation of peer educators is carried out by Puskesmas staff. 001 (<0.05). There are differences in the level of knowledge and attitudes of adolescents with p-value = 0.001 (<0.05). The group that has the most influence on adolescent knowledge is the control group, p-value 0.014 (<0.05). Meanwhile, the attitude of adolescents does not exist because the p-value is 0.502 (> 0.05). Suggestion: regular training, monitoring and evaluation of peer educators is carried out by Puskesmas staff. 001 (<0.05). There are differences in the level of knowledge and attitudes of adolescents with p-value = 0.001 (<0.05). The group that has the most influence on adolescent knowledge is the control group, p-value 0.014 (<0.05). Meanwhile, the attitude of adolescents does not exist because the p-value is 0.502 (> 0.05). Suggestion: regular training, monitoring and evaluation of peer educators is carried out by Puskesmas staff. ABSTRAK Satu dari pandemi paling mematikan adalah HIV/AIDS. Pada tahun 2020, sebanyak 680.000 orang meninggal karena terkait penyakit AIDS dan 1,5 juta orang baru terinfeksi HIV. (UNAIDS, 2021). Presentase kasus HIV/AIDS menurut kelompok umur kelompok umur produktif (15-49 tahun) sebesar 2,9 % mendominasi sebaran kasus baik HIV maupun AIDS.(KEMENKES RI, 2021). Kasus HIV/AIDS terus meningkat pada remaja sehingga pentingnya pengetahuan remaja dalam pencegahan HIV/AIDS. Salah satu metode yang digunakan yaitu peran peer educator, nakes memiliki tupoksi memberikan edukasi ke sekolah. Bertitik tolak hal tersebut pendekatan penyuluhan sehingga dapat merubah proses pikir, perasaan dan perilaku sehat. Tujuan penelitian mengetahui perbedaan tingkat pengetahuan dan sikap remaja tentang HIV/AIDS sebelum dan sesudah dilakukan edukasi peer educator, nakes dan kontrol di SMAN2 Kecamatan TBT. .Jenis penelitian kuantitatif dengan pendekatan “Quasi eksperiment” melakukan pengukuran sebelum dan sesudah dilakukan edukasi peer educator, nakes, kontrol. Populasi sejumlah 314 siswa. Teknik pengambilan sampel menggunakan simple random sampling 90 siswa dibagi 3 kelompok yaitu kelompok peer educator, nakes, kontrol. Instrument penelitian kuesioner dari SDKI tahun 2017. Analisis dilakukan dengan univariat, bivariat dan multivariat, Hasil penelitian ada pengaruh peningkatan pengetahuan dan sikap remaja tentang HIV/AIDS dengan nilai p-value = 0,001 (<0,05). Ada perbedaan tingkat pengetahuan dan sikap remaja dengan nilai p-value = 0,001 (<0,05). Kelompok yang paling berpengaruh terhadap pengetahuan remaja adalah kelompok kontrol p-value 0,014(<0,05). Sedangkan terhadap sikap remaja tidak ada karena p-value 0,502(>0,05). Saran: dilakukan pelatihan secara berkala, monitoring dan evaluasi kepada peer educator oleh petugas Puskesmas.